Simulation and Analysis of Hatchback Car Driving Comfort and Handling Performance - Yamin, Mohamad; Mahandari, Cokorda Prapti; Mumtaz, Mega Maulida (Journal of Novel Engineering Science and Technology, 2023)
Hatchback cars are one type of car that is widely used in Indonesia. Indonesia has various road conditions. What is essential for a vehicle is its driving comfort and handling performance. These aspects are not only to fulfil individual interests but also to increase safety while driving.   The driving comfort can be tested through the chassis twisted road test, and the handling performance is tested through the double lane change test. Both tests are carried out by simulation with the CarSim software that applies mathematical modelling. The driving comfort is tested with a speed variation of 8 km/h to 16 km/h. Handling performance was tested with variations in loading of 1 passenger, four passengers, and four passengers + luggage. The parameters used to measure driving comfort are vertical acceleration, pitch, and roll angle. The parameters for handling performance are lateral acceleration, yaw and roll angle, and sheer force. The results show that the best driving comfort is obtained at 8 km/h. The handling performance value will improve if the vehicle load decreases.